2012
DOI: 10.1016/j.actamat.2012.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoluminescence in BaSi2O2N2:Eu

Abstract: Mechanoluminescence (ML), a general term for the phenomenon in which light emission occurs during any mechanical action on a solid, can be divided roughly into two classes: destructive ML and non-destructive ML. For practical use in high-end applications (e.g. pressure sensors), materials with non-destructive ML properties are preferred. This paper reports on the strong non-destructive ML in BaSi 2 O 2 N 2 :Eu. When irradiated in advance with UV or blue light, this phosphor shows intense blue-green light emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 29 publications
4
104
0
Order By: Relevance
“…As the Cu concentration increased from 0% to 12%, the variation in the a axis (ranging from 3.7619 to 3.7634 Å ), c-axis (ranging from 11.4082 to 11.4119 Å ), and lattice volume, V (ranging from 139.8192 to 139.9754 Å 3 ) remained stable in a narrow range because Zn 21 (0.60 Å , CN 5 4) 28,29 was substituted with Cu 1 (0.60 Å , CN 5 4) 30,31 , which has a similar ionic radius. X-ray photoelectron spectroscopy showed that the CaZnOS was doped with Cu 1 , which also confirmed that the Cu 1 was doped into the Zn 21 site of the CaZnOS crystal structure; it was difficult to Mechanical quenching swaps to mechanoluminescence D Tu et al 2 substitute Cu 1 into the Ca 21 site because of the large radius mismatch of Ca 21 (1.00 Å , CN 5 6) 32 . According to the XRD refinement results, CaZnOS:Cu maintained its original crystal structure, even at a Cu concentration of 12%, and it possessed a noncentrosymmetric layered structure with a space group of P6 3 mc (inset in Figure 2).…”
Section: Resultsmentioning
confidence: 75%
“…As the Cu concentration increased from 0% to 12%, the variation in the a axis (ranging from 3.7619 to 3.7634 Å ), c-axis (ranging from 11.4082 to 11.4119 Å ), and lattice volume, V (ranging from 139.8192 to 139.9754 Å 3 ) remained stable in a narrow range because Zn 21 (0.60 Å , CN 5 4) 28,29 was substituted with Cu 1 (0.60 Å , CN 5 4) 30,31 , which has a similar ionic radius. X-ray photoelectron spectroscopy showed that the CaZnOS was doped with Cu 1 , which also confirmed that the Cu 1 was doped into the Zn 21 site of the CaZnOS crystal structure; it was difficult to Mechanical quenching swaps to mechanoluminescence D Tu et al 2 substitute Cu 1 into the Ca 21 site because of the large radius mismatch of Ca 21 (1.00 Å , CN 5 6) 32 . According to the XRD refinement results, CaZnOS:Cu maintained its original crystal structure, even at a Cu concentration of 12%, and it possessed a noncentrosymmetric layered structure with a space group of P6 3 mc (inset in Figure 2).…”
Section: Resultsmentioning
confidence: 75%
“…This process is non-destructive, and can be repeated by illuminating the material with blue or UV light after the mechanical stimulus. The occurrence of mechanoluminescence in BaSi 2 O 2 N 2 :Eu is related to its specific crystallographic structure and to the presence of many defects, as witnessed from the long afterglow in this compound [39]. Compared to the steady state photoluminescence spectrum, the ML emission spectrum is shifted by about 4nm to longer wavelengths.…”
Section: Overview Of Oxynitride Phosphorsmentioning
confidence: 94%
“…In addition, it also shows a strong mechanoluminescence (ML, also known as elasticoluminescence) [39]. Upon application of pressure or friction, light is emitted if the material was previously exposed to (short wavelength) light having the ability to fill traps [65,66].…”
Section: Overview Of Oxynitride Phosphorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One type of mechano-optical conversion, ML which emits light induced by dynamic stress, has drawn much attention and has been reported in many inorganic compounds, for instance ZnS:Cu, 14,15 SrMg 2 (PO 4 ) 2 :Eu (blue), 16 SrAl 2 O 4 :Eu, [11][12][13][17][18][19] BaSi 2 O 2 N 2 :Eu (green), 20,21 CaZnOS:Mn, 22 Sr nþ1 Sn n O 3nþ1 :Sm (red), 23 and so on. However, the phosphorescent performances of these compounds have not been fully utilized for sensing the stress.…”
mentioning
confidence: 99%